Lysosomal Dysfunction and α-Synuclein Aggregation in Parkinson's Disease: Diagnostic Links - Moors, Tim; Paciotti, Silvia; Chiasserini, Davide; Calabresi, Paolo; Parnetti, Lucilla; Beccari, Tommaso; van de Berg, Wilma D. J. (Movement disorders, 2016)
ABSTRACT Lysosomal impairment is increasingly recognized as a central event in the pathophysiology of PD. Genetic associations between lysosomal storage disorders, including Gaucher disease and PD, highlight common risk factors and pathological mechanisms. Because the autophagy–lysosomal system is involved in the intralysosomal hydrolysis of dysfunctional proteins, lysosomal impairment may contribute to α‐synuclein aggregation in PD. The degradation of α‐synuclein is a complex process involving different proteolytic mechanisms depending on protein burden, folding, posttranslational modifications, and yet unknown factors. In this review, evidence for lysosomal dysfunction in PD and its intimate relationship with α‐synuclein aggregation are discussed, after which the question of whether lysosomal proteins may serve as diagnostic biomarkers for PD is addressed. Changes in lysosomal enzymes, such as reduced glucocerebrosidase and cathepsin levels, have been observed in affected brain regions in PD patients. The detection of lysosomal proteins in CSF may provide a read‐out of lysosomal dysfunction in PD and holds promise for the development of diagnostic PD biomarkers. Initial PD biomarker studies demonstrated altered lysosomal enzyme activities in CSF of PD patients when compared with controls. However, CSF lysosomal enzyme activities alone could not discriminate between PD patients and controls. The combination of CSF lysosomal markers with α‐synuclein species and indicators of mitochondrial dysfunction, inflammation, and other pathological proteins in PD may be able to facilitate a more accurate diagnosis of PD. Further CSF biomarker studies are needed to investigate the utility of CSF lysosomal proteins as measures of disease state and disease progression in PD. © 2016 International Parkinson and Movement Disorder Society